Federation in Australia - Shaw, Alan G. L. (Czasopismo Prawno-Historyczne, 1980)
The Commonwealth of Australia, as a Federation, came into existence on 1 January, 1901. It was made up of the six pre-existing British colonies, New South Wales, Tasmania, Western Australia, South Australia, Victoria and Queensland, to list them in the chronological order of their foundation. Situated as they were in a remote quarter of the globe, during the nineteenth century they were isolated from the mainstream of world events. As colonies, they retained a formal dependence upon the United Kingdom, although they contributed nothing to her budget and had complete freedom in regard to their internal affairs. But they were not independent nations. They had no international sovereignty. They could not conduct their own foreign policy, declare war or make peace; when the mother country was at war, they were at war too. They depended entirely on the United Kingdom for their defence, though because of their isolated position they were not greatly worried by fear of attack. Their skeleton forces were maintained almost entirely to deal with any threat of local disorders, and as an incidental result of this, their expenditure on defence was low.